Maternal chlormequat chloride exposure disrupts embryonic growth and produces postnatal adverse effects. (September 2020) - Xiagedeer, Bayindala; Hou, Xiaohong; Zhang, Qi; Hu, Hong; Kang, Chenping; Xiao, Qianqian; Hao, Weidong
Highlights: Maternal exposure of chlormequat chloride at 5 mg/kg. bw increased embryonic growth parameters through elevating embryonic GH level. Maternal exposure of chlormequat chloride at 5 mg/kg bw has adverse effects on postnatal health . The safety of current official ADI for chlormequat chloride might be doubtful. Abstract: We showed previously that chlormequat chloride, a widely used plant growth regulator, could affect embryonic growth and growth hormone (GH)-insulin-like growth factor 1 (IGF-1) axis of rats. However, the potential effects of low dose chlormequat chloride exposure during pregnancy on embryonic and postnatal growth and development remain unclear. To further assess the risk of chlormequat chloride to human embryonic growth and postnatal health, we exposed maternal rats orally to the chemical during pregnancy at 5 mg/kg bw, a dose corresponding to the human acceptable daily intake (ADI) level set by World Health Organization (WHO), and determined the effects of chlormequat on embryo growth and postnatal health. We found that chlormequat chloride increased embryonic growth parameters, GH, and GH-releasing hormone (GHRH) levels, but did not affect somatostatin and IGF-1 on gestational day (GD) 11. In the pups of postnatal day (PD) 7, we observed increased head length, decreased body fat percentage, hypoglycemia, hyperlipidemia and hyperproteinemia. In conclusion, maternal exposure to chlormequat chloride during pregnancy disrupts the embryonic growth probably through its effects on growth regulators and even has adverse effects on postnatal health.